Toe Transfers in Mutilated Hands: Technical Considerations To Get Good Outcomes - Shanmuganathan Raja Sabapathy, MCh, FRCS; Hari Venkatramani, MS, MCh; Praveen Bhardwaj, MS, FNB; Monusha Mohan, MS, FNB; Vigneshwaran Varadharajan, MS, FNB (Journal of Hand Surgery Global Online)
In severe mutilating injuries of the hand, microvascular toe transfers can help gain prehension. Radical debridement and primary wound healing, with or without a flap cover, are the prerequisites for a successful toe transfer. A pedicled groin flap is our preferred method of soft tissue cover. A primary toe transfer can be performed in cases of isolated thumb loss. The metacarpophalangeal joint should be preserved whenever possible. The first web space should be maintained to obtain optimal results. In cases where two toe transfers are required, the authors prefer to do them in two sittings; the thumb is reconstructed first, followed by finger reconstruction. A great toe is used for thumb reconstruction in patients where a part of the palm and multiple fingers are lost. Proper positioning of the thumb and high quality of tendon and nerve repair followed by adequate hand therapy will lead to ideal outcomes.